2006
DOI: 10.1007/s11160-006-9020-z
|View full text |Cite
|
Sign up to set email alerts
|

Feeding habits of the blue shark, Prionace glauca, and salmon shark, Lamna ditropis, in the transition region of the Western North Pacific

Abstract: We describe the feeding habits of 70 blue sharks (Prionace glauca) and 39 salmon sharks (Lamna ditropis) caught at 0-7 m depth at night by research drift gillnets in the transition region of the western North Pacific during AprilMay of 1999 and 2000. Blue sharks of 50-175 cm total length fed on a large variety of prey species, consisting of 24 species of cephalopods and 16 species of fishes. Salmon sharks of 69-157 cm total length fed on a few prey species, consisting of 10 species of cephalopods and one speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
2
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 13 publications
5
52
2
5
Order By: Relevance
“…In response to disturbance caused by the submersibles, Stauroteuthis syrtensis inflated its web complex and exhibited the ballooning behavior noted previously (Vecchione & Young 1997, Johnsen et al 1999. Thus, observations in the present study supported the hypothesis that these behaviors may function as an alarm response to deter or confuse predators, such as Cuvier's beaked whales Ziphius cavirostris and blue sharks Prionace glauca (Vecchione & Young 1997, Johnsen et al 1999, Santos et al 2001, Kubodera et al 2007. Observations also indicated that slow sculling of the paired fins, medusoid contractions of the web, and rapid fin sculling were similar to patterns of locomotion reported for another deep-water cephalopod, Vampyroteuthis infernalis (Seibel et al 1998).…”
Section: Discussionsupporting
confidence: 87%
“…In response to disturbance caused by the submersibles, Stauroteuthis syrtensis inflated its web complex and exhibited the ballooning behavior noted previously (Vecchione & Young 1997, Johnsen et al 1999. Thus, observations in the present study supported the hypothesis that these behaviors may function as an alarm response to deter or confuse predators, such as Cuvier's beaked whales Ziphius cavirostris and blue sharks Prionace glauca (Vecchione & Young 1997, Johnsen et al 1999, Santos et al 2001, Kubodera et al 2007. Observations also indicated that slow sculling of the paired fins, medusoid contractions of the web, and rapid fin sculling were similar to patterns of locomotion reported for another deep-water cephalopod, Vampyroteuthis infernalis (Seibel et al 1998).…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, studies utilizing stomach contents to examine the feeding chronology of large-bodied species almost exclusively focus on neonates and juveniles (e.g. Medved et al 1985, Cortés & Gruber 1990, Bush 2003, Barry et al 2008, Kubodera et al 2007, TorresRojas et al 2010, with the notable exception of Barnett et al (2010) who examined stomachs from all size classes of broadnose sevengill sharks Noto rhynchus cepedianus. Conversely, our method includes all life stages that are susceptible to longline gear.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Sciarrotta & Nelson (1977) tracked 14 blue sharks Prionace glauca in the eastern Pacific Ocean and found these sharks to be most active during nocturnal periods, as indicated by increased frequency of dives through the water column. This finding led the authors to conclude that while blue sharks feed during all hours of the day, peak feeding occurs at night; however, based on analyses of stomach contents, Kubodera et al (2007) concluded that blue sharks in the western Pacific Ocean feed primarily during the day.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that stable isotope composition of juvenile sharks reflects use of the NPTZ nursery. The NPTZ is a dynamic and productive oceanic region bounded by the subarctic and subtropical frontal zones that has been shown to be an important foraging area and migratory corridor for a variety of pelagic predators [42], including juvenile salmon sharks [12,35]. rspb.royalsocietypublishing.org Proc.…”
Section: (A) Nursery and Juvenile Habitatsmentioning
confidence: 99%